Japanese management techniques to enhance the governance of Greek small and medium-sized firms - Enrique Yacuzzi (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2012)
Given the economic and social crisis Greece is going through, it seems clear that the Greek future over the next few years will rest on macroeconomic actions, both national and international. This undeniable assertion notwithstanding, I do maintain that the Greek private sector has an important role to play in overcoming the present crisis. This especially applies to Greek small and medium-sized enterprises (SMEs), which comprise an important proportion of Greek firms. The use of adequate SME governance tools at Greek companies might be beneficial. Good governance leads to a better relationship among stakeholders, increases the effectiveness of board work and activates unknown potential at the firm through better principles and practices. Some Japanese tools that enhance governance as could be applied to Greek SMEs and smaller state organizations are presented. In general, SMEs, with fewer relative resources, face important conceptual and methodological difficulties when implementing a governance structure. This assertion is also true in Greece. Over the past three or four decades, however, Japanese management techniques that can be applied to implement and consolidate SME governance have gained diffusion all over the world. These tools are particularly apt for Greek SMEs, due to their flexibility, low cost, and rapid effectiveness. Specific examples of applications to enhance governance at Greek SMEs are provided. Tools applied are (1) A new SME governance indicator; (2) Hoshin management; and (3) Effective meeting technology. The three tools interact in a systemic mode.
Keywords: 330; KMU; Führungsstil; Japanisch; Griechenland